1999
DOI: 10.1089/cpb.1999.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in the Use of Virtual Environments

Abstract: Gender differences in cognitive and behavioral performance have been reported throughout the psychological literature. Consequently, gender differences should be considered and controlled for when cognitive research is conducted in virtual environments (VEs). These variables may include gender-related differences in cognitive performance, susceptibility for cybersickness, and the impact of sex hormones on cognition. Such issues are addressed in the context of a recent VE study of the visuospatial ability refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…Parsons et al [32] speculated that the strategies employed by males and females were different which yielded differences in performance. Parsons et al [32], Larson et al [33], and Rizzo and Buckwalter [34], tested gender differences for mental rotation in virtual environments and found that gender difference for mental rotation vanishes in virtual environments. In our studies, we considered that spa- tial ability might be a moderator of performance, so we measured this beforehand with a 2D Vandenberg and Kuse mental rotation test [35].…”
Section: Learning Transfer In a Virtual Environmentmentioning
confidence: 99%
“…Parsons et al [32] speculated that the strategies employed by males and females were different which yielded differences in performance. Parsons et al [32], Larson et al [33], and Rizzo and Buckwalter [34], tested gender differences for mental rotation in virtual environments and found that gender difference for mental rotation vanishes in virtual environments. In our studies, we considered that spa- tial ability might be a moderator of performance, so we measured this beforehand with a 2D Vandenberg and Kuse mental rotation test [35].…”
Section: Learning Transfer In a Virtual Environmentmentioning
confidence: 99%
“…Related literature reports on notable individual differences in spatial behavior attributable to computer experience (Wingrave et al 2005), gender (Larson et al 1999;Waller 2000) and spatial abilities (Luursema et al 2008;Rizzo et al 2000). Relevant research includes comparing spatial information transfer of virtual environments to the real world (Waller et al 2001) and real world studies such as selecting objects with a laser pointer (Myers et al 2002).…”
Section: Related Workmentioning
confidence: 99%
“…Many studies have shown that experiential factors, including computer and videogame usage, are related to spatial skill, such as mental rotation (MR;De Lisi & Cammarano, 1996;De Lisi & Wolford, 2002;Duesbury & O'Neil, 1996;Larson et al, 1999;McClurg & Chaille, 1987;Okagaki & Frensch, 1994;Rizzo et al, 1999;Roberts & Bell, 2000;Saccuzzo, Craig, Johnson, & Larson, 1996;Sims & Mayer, 2002). Likewise, studies that were focused on the impact of training with computers (including videogames) have shown increases spatial ability.…”
mentioning
confidence: 99%
“…Elevated performance on spatial tasks has even been elicited by simply facilitating familiarity with computers Roberts & Bell, 2000). However, some studies have shown that both men and women can benefit from computer experience, such as videogame playing (De Lisi & Cammarano, 1996;Dorval & Pepin, 1986;Larson et al, 1999;Lawton & Morrin, 1999;McClurg & Chaille, 1987;Okagaki & Frensch, 1994;Subrahmanyam & Greenfield, 1996). Thus, it is reasonable to conclude that computer usage (including videogame playing) can increase spatial aptitude in both men and women, though perhaps rates of improvement may differ.…”
mentioning
confidence: 99%